Effect of reaction temperature on steam methane reforming’s yield over coated nickel aluminide (Ni3Al) catalyst in micro reactor - Madon, Rais Hanizam; Mas Fawzi, Mas Fawzi; Sarwani, Muhamad Khairul Ilman; Osman, S.A.; Razali, Mohd Azahari; Mohammad, Abdul Wahab (Penerbit Akademia Baru, 2018)
This work investigates the effect of reaction temperature on methane conversion and hydrogen yield over coated Nickel Aluminide (Ni3Al) as an intermetallic alloy catalyst in micro reactor. The Ni3Al was impregnated at micro scale using dip coating technique. The coating impregnation process, consist of a few stages which are substrates and solgel preparation, dip coating, calcination and reduction of oxide molecule. The coated Ni3Al were characterized by X-Ray Diffraction (XRD) and Temperature Programming Reduction (TPR) then activated using H2. The XRD and TPR results showed present of Ni3Al on the coated surface and was successfully activated at 500°C and 46 minutes. Meanwhile, the steam methane reforming with the catalytic reaction took place at temperature from 500°C to 700°C, steam to carbon ratio of 3:1 and 5 hours reaction time. The reaction temperature of 600°C obtained the highest methane conversion of 43% and hydrogen yield of 29%. The limitation point of reaction activity either as zero reaction or deactivation point was found at 500°C and 700°C. The coated Ni3Al showed catalytic activity for each reaction temperature and work accordingly on the heterogenous catalyst principal theory of lag, exponential, stationary and deactivation stage.